GURU KRISTEN SEBAGAI PENUNTUN BELAJAR SISWA KELAS XII DI SATU SEKOLAH KRISTEN [CHRISTIAN TEACHERS AS GUIDES TO LEARNING FOR GRADE 12 STUDENTS AT ONE CHRISTIAN SCHOOL] - Gultom, Ester Lusia; Sitompul, Henni; Tamba, Kimura Patar (Universitas Pelita Harapan, 2019)
The implementation of the 2013 curriculum aims to improve the quality of Indonesian education by enabling students to develop competencies. Therefore, it is expected that students actively learn in the classroom so that effective learning processes are created to develop student competencies. However, based on facts found in grade 12 at one of the Christian schools in Cibubur, students were not actively studying in class. Christian teachers see this gap as something that can be corrected with competencies they can guide. God calls Christian teachers to guide students who have fallen into sin to return to God's path with the proper competence, direction, and purpose. Thus, the purpose of this paper is to present the role of a Christian teacher as a guide to learning for grade 12 students in one Christian school, as well as the resulting impact. The results of this paper about the role of Christian teachers as guides, who view students as precious and personal creations before the Lord, show that teachers are able to guide according to the needs of students using the Discovery Learning model and supporting methods such as group discussion methods, lectures, FAQs, and games. Suggestions aimed at Christian teachers may provide learning guidance for using the Discovery Learning model and its supporting methods.BAHASA INDONESIA ABSTRAK: Penerapan kurikulum 2013 bertujuan untuk meningkatkan kualitas pendidikan Indonesia dengan cara memampukan siswa untuk mengembangkan kompetensi. Oleh karena itu, diharapkan siswa bisa aktif belajar di kelas sehingga dapat diciptakan proses pembelajaran yang efektif untuk mengembangkan kompetensi siswa. Namun, berdasarkan fakta yang ditemukan di kelas XII pada salah satu sekolah Kristen di Cibubur, ditemukan siswa yang masih kurang aktif belajar di kelas. Guru Kristen melihat kesenjangan ini sebagai hal yang harus diperbaiki dengan kompetensi yang dimilikinya sebagai penuntun. Karena Tuhan memanggil guru Kristen untuk menuntun siswa yang telah jatuh dalam dosa supaya kembali ke jalan Tuhan, dengan kompetensi, arah, dan tujuan yang benar. Maka, tujuan penulisan paper ini adalah memaparkan peran guru Kristen sebagai penuntun belajar siswa kelas XII di satu sekolah Kristen, serta dampak yang dihasilkan. Hasil paper ini mengenai peran guru Kristen sebagai penuntun yang memandang siswa sebagai ciptaan sekaligus pribadi yang berharga di hadapan Tuhan sehingga guru mampu menuntun sesuai dengan kebutuhan siswa, menggunakan model pembelajaran Discovery Learning serta metode pendukungnya seperti metode diskusi kelompok, ceramah, tanya jawab, dan permainan. Saran ditujukan kepada guru Kristen kiranya dapat memberikan tuntunan belajar yang sesuai dengan kebutuhan salah satunya menggunakan model Discovery Learning serta metode pendukungnya.